2014
DOI: 10.1007/s10484-014-9253-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation/Exhalation Ratio Modulates the Effect of Slow Breathing on Heart Rate Variability and Relaxation

Abstract: Slow breathing is widely applied to improve symptoms of hyperarousal, but it is unknown whether its beneficial effects relate to the reduction in respiration rate per se, or, to a lower inhalation/exhalation (i/e) ratio. The present study examined the effects of four ventilatory patterns on heart rate variability and self-reported dimensions of relaxation. Thirty participants were instructed to breathe at 6 or 12 breaths/min, and with an i/e ratio of 0.42 or 2.33. Participants reported increased relaxation, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
138
5
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(173 citation statements)
references
References 50 publications
(64 reference statements)
13
138
5
5
Order By: Relevance
“…Our findings of a significant decrease in SDNN, RMSSD, LF and HF with CPAP therapy in patients with CSA may be attributed to the normalized breathing pattern during the night in those patients, since these parameters are strongly dependent on respiration frequency and depth . In concordance with that explanation is the presence of a significant strong correlation between the decrease in AHI and in lnHF (influenced strongly by breathing pattern) with the application of CPAP. Similar results with a decrease in HRV parameters after CPAP application were found by Kufoy et al.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings of a significant decrease in SDNN, RMSSD, LF and HF with CPAP therapy in patients with CSA may be attributed to the normalized breathing pattern during the night in those patients, since these parameters are strongly dependent on respiration frequency and depth . In concordance with that explanation is the presence of a significant strong correlation between the decrease in AHI and in lnHF (influenced strongly by breathing pattern) with the application of CPAP. Similar results with a decrease in HRV parameters after CPAP application were found by Kufoy et al.…”
Section: Discussionsupporting
confidence: 83%
“…Generally speaking, we know that HRV is higher when exhalations last longer than inhalations (Strauss-Blasche et al, 2000). Furthermore, in a study investigating specifically the effect of the i/e ratio when breathing at 6 breaths/min (Diest et al, 2014), participants reported more relaxation, positive energy, stress reduction, and mindfulness with a low i/e ratio (exhales > inhales), compared to a high i/e ratio (inhales > exhales). In the present study, the i/e ratio was set to 40/60, meaning that inhalation lasted 3.7 s and exhalation 5.5 s.…”
Section: Resonance Frequency Breathing (Rfb)mentioning
confidence: 97%
“…Regarding adequacy of ventilation, we expected that paced breathing will decrease PetCO 2 . On the basis of previous studies, we did not expect that breathing at 0.1 Hz would affect mean heart rate (Cappo & Holmes, ; McCaul et al, ; van Diest et al, ). In line with the well‐established effects of breathing frequency on RSA, we expected increased RSA during breathing at 0.1 Hz.…”
Section: Introductionmentioning
confidence: 91%
“…Cappo and Holmes () measured the effects of breathing at 0.1 Hz before the eliciting of negative emotions and reported null findings. Van Diest et al () reported that participants had lower affective arousal after breathing at 0.1 Hz in comparison to 0.2 Hz. Recently, Steffen, Austin, DeBarros, and Brown () reported no effect on anxious arousal but increased positive mood.…”
Section: Introductionmentioning
confidence: 99%